Inocybe griseorubida, a new species of Pseudosperma clade from tropical India - Latha, K. P. Deepna; Manimohan, Patinjareveettil (Phytotaxa, 2015)
Inocybe griseorubida sp. nov. is described from Kerala State, India. A comprehensive description, photographs, and comparisons with phenetically similar species are provided. The nuclear ribosomal internal transcribed spacer region (ITS), a portion of the nuclear ribosomal large subunit (nLSU) and a portion of the nuclear second-largest subunit of RNA polymerase II (rpb2) gene of this species were sequenced and analyzed. Phylogenetic analysis of rpb2 sequences confirmed both the novelty of the species and its placement within the Pseudosperma clade.